RISK MANAGEMENT IN PROJECTS OF RESTORATION THE REGIONAL TRANSPORT STRUCTURE ON THE BASIS OF PARTICIPANTS' COMMUNICATION - Lytvynenko, Dmytro; Malyeyeva, Olga (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2022)
The subject of the article is the processes of risk management and project communications. The components of the content of transport infrastructure rehabilitation projects, including communications between stakeholders, are considered. The aim of the work is to develop a method for assessing and managing the risks in transport infrastructure rehabilitation projects, taking into account the communication processes of the participants. The following tasks are solved in the article: systematization of risks in transport infrastructure rehabilitation projects in the form of relations between the project participants, creation of a graphic scheme of stakeholder communications, formalization of stakeholder communications with regard to the causes and possible parry of risks, development of a quantitative assessment model of the project risks with regard to stakeholder interests. Methods used: project management methodology, stakeholder theory, value theory, systems approach, matrix models. The following results were obtained: Opportunities, impact and risk status in relation to stakeholders of the transport infrastructure rehabilitation project were analyzed. The possibility of grouping risks in relation to the stakeholders of the project and the possibility of influence of stakeholder interaction on the available risk groups were considered. The risks that can directly affect the project or be affected by the interaction between the project stakeholders were identified. The formalized representation of risks and communications of project participants is presented. Opportunities to optimize the process of project risk management through the management of stakeholders and project communications have been identified. Quantitative project risk value model was developed to assess the effectiveness of actions to parry risks from stakeholders. Conclusions: project risk management can be more effective if tools and methods specific to stakeholder management and project communications are applied. The proposed formalization establishes a clear model of stakeholder interaction to parry risks. The model of quantitative assessment of the effectiveness of actions to parry risks will allow to evaluate the effectiveness of the management strategy and to make adjustments in time. In the future, this work will continue scientific research in the direction of developing models and methods of research of communications and risks of the project